2008
DOI: 10.1021/bc700308q
|View full text |Cite
|
Sign up to set email alerts
|

Antibody−Dendrimer Conjugates: The Number, Not the Size of the Dendrimers, Determines the Immunoreactivity

Abstract: Radioimmunotherapy using antibodies with favorable tumor targeting properties and high binding affinity is increasingly applied in cancer therapy. The potential of this valuable cancer treatment modality could be further improved by increasing the specific activity of the labeled proteins. This can be done either by coupling a large number of chelators which leads to a decreased immunoreactivity or by conjugating a small number of multimeric chelators. In order to systematically investigate the influence of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 29 publications
2
76
0
1
Order By: Relevance
“…The outcome of the present work presents the use of antibodies such as poly or monocolonal (polyclonal goat anti-rabbit antibody, anti-EGFR antibody hmab425 or conjugated to PAMAM different generation dendrimer or C595 targeted alpha radiotherapy) as anticancer or immunological biomolecules [23][24][25][26]. As a result of observed confirmations from the present research, Gd 3+ -ALGD-G 2 -C595 nano-probe is a potential dual selective breast molecular imaging and therapeutic agents and seems to be a good functional nano-probe and it should to be further studied by clinical trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome of the present work presents the use of antibodies such as poly or monocolonal (polyclonal goat anti-rabbit antibody, anti-EGFR antibody hmab425 or conjugated to PAMAM different generation dendrimer or C595 targeted alpha radiotherapy) as anticancer or immunological biomolecules [23][24][25][26]. As a result of observed confirmations from the present research, Gd 3+ -ALGD-G 2 -C595 nano-probe is a potential dual selective breast molecular imaging and therapeutic agents and seems to be a good functional nano-probe and it should to be further studied by clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…The advantage for the anionic linear dendrimer G 2 is regarding its PEG core which makes it mostly attractive to cancerous cells as well as anticancer effects [23][24][25][26]. The next interesting capability of anionic linear dendrimer G 2 is regarding its citric acid shell which raise potent Gd 3+ complex formation and Gd 3+ loading as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds bound to dendrimers can improve the surface activity as well as their biological and physical properties. Several specific ligands can be adsorbed, including folic acid, 203 antibodies, 204 target cyclic peptides containing arginine-glycine-aspartic acid, 205 and PEG. Studies involving nanotechnology and medically important fungi have demonstrated improvements in the antifungal properties, such as bioavailability, toxicity, and target tissue, for some drugs, such as AmB, which can facilitate innovative therapeutic approaches.…”
Section: Dendrimersmentioning
confidence: 99%
“…It is important to follow this sequence of reactions since if BODIPY is clicked first, followed by esterification with niacin, it leads to very poor yield of the product. Dendrimer size could be an important variable in designing dendrimer based conjugates depending on their intended application [35]. For instance, smaller generations such as in 4 which is estimated to be about 3e4 nm in size [36], with tailored active sites, are in fact desirable for nanodelivery carriers targeting different intracellular locations.…”
Section: Synthesis Of Nanocarriersmentioning
confidence: 99%